Mengungkap Nilai-Nilai Kearifan Lokal Kediri Sebagai Upaya Pelestarian Budaya Bangsa Indonesia - Kurnia, Ita (UNIB Press, 2018)
Indonesia is currently experiencing a national identity crisis. This is evidenced by the scientific study of the Indonesian Institute of Sciences (LIPI) that Indonesia is considered not ready to face the phenomenon of globalization in various aspects such as geography, economy, and culture. One effort that can be done by local communities as an effort to deal with the adverse effects of globalization is to use the values of local wisdom as a force. Local wisdom can serve as a filter for values that come from outside that are less suited to local cultural culture. This research is a qualitative research that express comprehensively some cases. The purpose of this research is to explore the potentials of local wisdom of Kediri people include (1) cultural background, (2) social background, and (3) agriculture and irrigation system in three subdistricts namely Kepung Subdistrict, Ngancar Subdistrict, and Semen Subdistrict. The results of this study indicate that (1) the majority of Kediri people are Javanese with strong Javanese custom by performing several rituals for nature conservation, (2) Kediri community social background with religious diversity but all goes well and peaceful and cultural preservation Strongly maintained, (3) the management of agricultural systems and irrigation society is very good and derived from generations of the Kediri kingdom proved by the existence of Harijing inscription.